Indefinities and bare nouns in generic contexts in European Portuguese - Oliveira, Fátima (2007)
The main goal of this work is to describe how singular and plural indefinites without modification in preverbal subject position behave in generic contexts and how they relate to bare nouns in European Portuguese (EP) in the same position and con- texts. In what concerns the distribution of bare nouns (BN) in subject preverbal position without modifiers, a contrast between Germanic and Romance languages has been noticed: plural count nouns and mass nouns are grammatical in English, but not in French and they are quite restricted in Italian, Spanish and EP. Based on the criteria established by Dowty (1979) for distinguishing states from events and on the distinction proposed by Cunha (2004) between phase and non phase eventualities, we establish a correlation between the distribution of BN and indefinites in preverbal subject position in EP and different types of predicates. Having summarized the patterns obtained by the data description, we combine (following Duarte et al., 2002, and Oliveira et al., 2006) the predicate value of each of the considered predicates and their corresponding subject value, in order to account for the properties of the BNs and indefinites preverbal subjects in EP, namely with respect to the generic contexts that allow them. It will be showed that both indefinites and BNs behave differently in such position depending on their singular or plural form.